Oproep tot steun aan de stakende mijnwerkers in Engeland door Adelmund in VARA's 'Rode Haan' - Adelmund, Karin. (1984)
Oproep tot steun aan de stakende mijnwerkers in Engeland door Adelmund in VARA's 'Rode Haan'.